Spectro-analytical Research of Selected Heavy Metals (Cu, Cd, Cr, and Pb) in Four Different Single-use Plastics Commonly in Contact with Food from Sokoto, Nigeria - Umar A.I.; Yusuf Sarkingobir; Dikko M. (Jurnal Teknokes, 2022)
Single use plastics are types of plastics discarded after one usage. They are everywhere you go because of their wide range of applications in life. In plastics, additives are incorporated to supplant properties of plastics. One of the common additives is the heavy metals, which could leach out along the plastics lifecycle, thereby creating a problem. This study was stimulated to determine the levels of heavy metals in selected single-use-plastics commonly in contact with food (as containers or wrappings or relations) in Sokoto. The Atomic Absorption Spectroscopy methodology was utilized to determine the levels of copper, chromium, lead, zinc and cadmium. The results for determination of selected heavy metals in selected single use plastics from Sokoto State University, Nigeria were revealed using atomic absorption spectroscopy. Therein, the concentrations of copper (Cu) ranges from 0.335+0.002 to 0.540+0.002(ug/kg), levels of cadmium (Cd) ranges from 0.0551+0.003 to 0.0041+0.0003(ug/kg), levels of chromium (Cr) ranges from 0.0959 +0.004 to 0.0265+0.001(ug/kg), levels of lead (Pb) ranges from -1.791+0.02 to -0.0706+0.008(ug/kg). Thus, the results revealed disparity in the levels of the analyzed heavy metals in the selected single use plastics. However, Cu concentration was the most elevated in plastic bottle (PB) and lowest in Takeaway (T); Cd was highest in Straw (S), and lowest in PB; Cr was highest in Ice cream cup (IC) and lowest in S; Pb was highest in PB, and lowest in S. The concentrations of Cupper, Chromium, Lead, and Cadmium in plastic bottle, Takeaway, Straw and lce cream cup, have shown disparity. However, Cu concentration was the most elevated in plastic bottle (PB) and lowest in Takeaway; Cd was highest in Straw, and lowest in PB; Cr was highest in Ice cream cup and lowest in S; Pb was highest in PB, and lowest in S. They levels determined are within the permissible limits.